Presidential hegemony and democratic backsliding in Latin America, 1925–2016. Issue 4 (19th May 2019) - Pérez-Liñán, Aníbal; Schmidt, Nicolás; Vairo, Daniela
ABSTRACT: Does the executive's institutional hegemony represent a risk to the survival of democracy? By hegemony, we refer to the president's ability to control other institutions, particularly the legislature and judiciary. To answer this question, we develop two indices of presidential hegemony and analyze the duration of democratic regimes in 18 Latin American countries between 1925 and 2016. The results show that executive hegemony is a major driver of democratic instability. This finding is robust to non-linear effects and to potential endogeneity in the relationship between presidential power and democratic backsliding. Our findings challenge traditional concerns about executive-legislative deadlock, and have significant implications for the nascent literature on democratic backsliding, which highlights executive aggrandizement as a risk factor.